A carbon nanotube / graphene / pyrolytic carbon composite material and preparation method thereof
By growing carbon nanotubes in situ in the graphene/nickel foam and filling with pyrolytic carbon, the brittleness and stability of traditional carbon fiber reinforced carbon composites are solved. High strength and lightweight performance improvements are achieved.
Patent Information
- Application Number
- CN202310233080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-10
AI Technical Summary
Traditional carbon fiber reinforced carbon matrix composites have problems such as high brittleness and poor service stability, which are mainly due to the weaving blind spots of the fiber preform, the damage to the tissue by graphitization treatment, and the performance losses caused by fiber cutting during molding.
The preparation method of carbon nanotubes/graphene/pyrolytic carbon composite materials was adopted to grow carbon nanotubes in situ in graphene/nickel foam by chemical vapor deposition method, and fill the pyrolytic carbon by precursor impregnation and cracking method to construct a macroscopic Carbon nanotubes-graphene multi-dimensional hybrid reinforcement.
Comprehensive modification and strengthening of the nanoscale of the carbon matrix has been achieved, the lightweight, high strength and multifunctional performance of carbon matrix composite materials have been improved, and the brittleness and stability of traditional materials have been solved.
Smart Images

Figure HDA0004121077680000011 
Figure HDA0004121077680000012 
Figure HDA0004121077680000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a carbon nanotube / graphene / pyrolytic carbon composite material and a preparation method thereof. Background Art
[0002] Carbon-based composite materials play an important role in high-tech fields such as aviation and aerospace due to their unique properties such as high temperature resistance, erosion resistance, ablation resistance, and excellent high-temperature mechanical properties. In recent years, with the rapid development of aerospace and national defense science and technology, the demand for lightweight, high-strength, and multifunctional carbon-based composite materials has become increasingly urgent. However, traditional carbon fiber reinforced carbon-based composites (C / C composites) have problems such as high brittleness and poor service stability. There are three main reasons for this: First, due to the micron-scale size of carbon fibers, there are weaving blind spots in the fiber preform, and the carbon matrix in multiple locations such as between layers, between single fibers within a layer, between fiber bundles, weaving gaps, and sharp corners of components lacks toughening; second, the carbon matrix that lacks toughening cannot effectively resist the continuous destruction of its organization by graphitization treatment, and is prone to structural defects such as annular cracking of the carbon matrix, interface weakening, and even debonding; third, during the molding process of C / C components, the composite material needs to be subjected to surface mechanical processing, which will inevitably cut off the carbon fibers in the three-dimensional woven structure, and the fiber aspect ratio drops sharply, which basically eliminates its toughening effect on the carbon matrix, especially for components with sharp corners, which will cause serious performance damage or "collapse" due to fiber cutting.
[0003] To solve this problem, the current stage mainly uses cross-scale reinforcement, such as graphene-carbon fiber cross-scale preforms and carbon nanotube-carbon fiber cross-scale reinforcements constructed by dispersing graphene or carbon nanotubes between fibers or in-situ grafting them on the fiber surface, as well as porous block materials that reach macroscopic scales in three directions by overlapping them by physical and chemical effects, such as graphene sponges, carbon nanotube arrays, and carbon nanotube aerogels. These two cross-scale preforms can perform multi-scale hybrid toughening (macroscopic, microscopic, and nanoscopic) on the composite matrix. However, research on the application of cross-scale reinforcements in carbon-based composites is only in its infancy, and there are very few reports on such research.
[0004] At present, the existing work focuses on the optimization of the structure and performance improvement of C / C composite materials by "carbon nanotube-carbon fiber cross-scale reinforcement". The research results show that carbon nanotubes can strengthen the fiber / matrix interface bonding and optimize the pyrolytic carbon at the micrometer scale, thereby improving the thermal conductivity and mechanical properties of C / C composite materials. The longer the carbon nanotubes are, the better the orientation is, the more significant the direct and indirect reinforcement effects on the pyrolytic carbon matrix are, and the greater the improvement in the mechanical properties of the corresponding C / C composite materials. The design of the nanocarbon-carbon fiber cross-scale structure was initially based on carbon fiber as the main reinforcement. The role of nanocarbon material as a secondary reinforcement greatly limits its huge potential reinforcement ability for carbon-based composite materials. In addition, carbon fiber is a micrometer-level reinforcement and cannot provide a mechanical reinforcement effect on the composite material at the nanoscale. A few research works have used carbon nanotube arrays to enhance carbon-based composites and their thermal conductivity studies, and their mechanical properties are limited by the macroscopic size of the carbon nanotube arrays. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a carbon nanotube / graphene / pyrolytic carbon composite material and a preparation method thereof. Compared with the nanocarbon-carbon fiber cross-scale reinforcement, the cross-scale reinforcement composed entirely of nanocarbon can comprehensively modify and strengthen the carbon matrix at the nanoscale, and also shows great advantages in achieving lightweight carbon-based composite materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a carbon nanotube / graphene / pyrolytic carbon composite material, comprising the following steps:
[0008] S1: preparing graphene / nickel foam;
[0009] S2: In situ growth of carbon nanotubes in graphene / nickel foam by injection chemical vapor deposition to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement;
[0010] S3: The carbon nanotube / graphene / pyrolytic carbon composite material is prepared by filling pyrolytic carbon into the carbon nanotube / graphene multidimensional hybrid reinforcement using a precursor impregnation pyrolysis method.
[0011] The present invention further states that in S1, the method for preparing the graphene / nickel foam is a chemical vapor deposition method, and the process of preparing the graphene / nickel foam by the chemical vapor deposition method is as follows:
[0012] S11: placing the nickel foam in hydrochloric acid for a first treatment, and then placing it in acetone for a second treatment to obtain a pretreated nickel foam;
[0013] S12: placing the pretreated nickel foam in a tubular furnace for a first heat treatment, growing graphene on the pretreated nickel foam, and obtaining graphene / nickel foam.
[0014] The present invention further, in said S12, the process of said first heat treatment is as follows:
[0015] The carbon source in the first heat treatment is methane or methanol, and the concentration of the carbon source in the first heat treatment is 0.5-3% of the total concentration of the mixed atmosphere; the mixed atmosphere in the first heat treatment is a mixed gas composed of the carbon source and hydrogen;
[0016] The growth temperature during the graphene growth process is 950-1100° C.;
[0017] The first heat treatment time is 3 to 10 minutes.
[0018] The present invention further comprises that in S2, the process of in-situ growing carbon nanotubes in graphene / nickel foam by injection chemical vapor deposition to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement is as follows:
[0019] S21: mixing anhydrous ethanol, ethylenediamine and deionized water uniformly to obtain a mixed solution, and then dissolving ferrocene in the mixed solution to obtain a precursor solution for growing carbon nanotubes;
[0020] S22: placing the graphene / nickel foam in a tube furnace for a second heat treatment, injecting a precursor liquid for growing carbon nanotubes into the graphene / nickel foam using an injection chemical vapor deposition process, to obtain a carbon nanotube / graphene / nickel foam;
[0021] S23: washing the carbon nanotube / graphene / nickel foam and freeze-drying it to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0022] The present invention further comprises that in S21, the volume ratio of anhydrous ethanol to ethylenediamine is (4-7):(1-5), the concentration of ferrocene is 0.02-0.032 g / ml; and the molar ratio of ferrocene to deionized water in the mixed solution is (1-10):(1-10).
[0023] The present invention further, in said S22, the process of said second heat treatment is as follows:
[0024] The carbon source in the second heat treatment is any one of toluene, ethanol, and acetone; the mixed atmosphere in the second heat treatment is a mixed gas composed of a carbon source and hydrogen; the concentration of the carbon source in the second heat treatment is 0.5 to 3% of the total concentration of the mixed atmosphere; the heat treatment temperature in the second heat treatment is 950 to 1100° C.; the reaction time in the second heat treatment is 0.5 to 12 hours;
[0025] In S23, the freeze-drying process time is 12 to 48 hours.
[0026] The present invention further discloses that in S3, the process of filling pyrolytic carbon in the carbon nanotube / graphene multidimensional hybrid reinforcement by the precursor impregnation pyrolysis method to prepare the carbon nanotube / graphene / pyrolytic carbon composite material is as follows:
[0027] S31: dissolving phenolic resin in ethanol to obtain a precursor solution for depositing a pyrolytic carbon matrix;
[0028] S32: Immersing the carbon nanotube / graphene multidimensional hybrid reinforcement in a precursor solution for curing, and then placing it in a tubular furnace for high-temperature cracking to obtain a carbon nanotube / graphene / pyrolytic carbon composite material.
[0029] The present invention further comprises that in said S31, the concentration of the phenolic resin in the precursor solution is 20-50% by mass;
[0030] In the S32, the process conditions of the curing are as follows:
[0031] The curing is carried out by oven curing; the oven curing temperature is 60 to 200° C.; the oven curing insulation time is 3 to 5 hours;
[0032] In S32, the process conditions of the high temperature cracking are as follows:
[0033] The temperature of the high temperature cracking is 800-1100° C., the time of the high temperature cracking is 0.5-3 hours, and the atmosphere of the high temperature cracking is one of argon and nitrogen or a mixture of the two in any ratio.
[0034] The present invention also provides a carbon nanotube / graphene / pyrolytic carbon composite material prepared by any one of the methods for preparing the carbon nanotube / graphene / pyrolytic carbon composite material.
[0035] The present invention further discloses that the apparent density of the carbon nanotube / graphene / pyrolytic carbon composite material is 1.4 to 1.8 g / cm 3 ; The porosity of the carbon nanotube / graphene / pyrolytic carbon composite material is 3 to 17%.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention proposes a method for preparing a carbon nanotube / graphene / pyrolytic carbon composite material, realizes in-situ growth of graphene foam and carbon nanotubes with specific morphological structures by means of chemical vapor deposition, realizes controllable preparation of graphene and carbon nanotubes in large-sized porous nickel foam, constructs a macroscopic carbon nanotube-graphene multidimensional hybrid reinforcement, designs and proposes to use it to reinforce pyrolytic carbon and prepare ultra-light nanocomposite materials; through morphology control and structural adjustment of the carbon nanotube-graphene multidimensional hybrid reinforcement, the microstructure of the carbon nanotube / graphene / pyrolytic carbon composite material can be regulated, and the comprehensive performance of the carbon nanotube / graphene / pyrolytic carbon composite material can be improved through effective structural regulation, providing technical support and theoretical basis for the preparation and development of new lightweight, multifunctional integrated, high-strength and tough carbon-based composite materials; the ultra-low density carbon nanotube-graphene multidimensional hybrid reinforcement will give the carbon nanotube / graphene / pyrolytic carbon composite material an ultra-light weight ratio.
[0038] The three-dimensional carbon nanotube / graphene / pyrolytic carbon composite material described in the present invention is a cross-scale reinforcement composed entirely of nanocarbon, which comprehensively modifies and strengthens the carbon matrix on the micron scale. Compared with traditional nanocarbon-carbon fiber cross-scale reinforcements, the three-dimensional nanomaterial has a more effective reinforcement and toughening effect, and can improve the strength, toughness and lightweight of carbon-based composite materials at the same time, which is of great significance to improving the carrying capacity of aerospace vehicles and reducing flight costs.
[0039] The invention discloses a carbon nanotube / graphene / pyrolytic carbon composite material prepared according to a preparation method, which has the advantages of light weight, high strength and toughness, and multifunctional integration. The carbon nanotubes are in-situ grown in the graphene / nickel foam with a macroscopic three-dimensional skeleton of graphene / nickel foam to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement with graphene foam as a reinforcement skeleton and carbon nanotubes interspersed in foam micropores. The carbon nanotube / graphene multidimensional hybrid reinforcement is densified by chemical vapor infiltration and finally graphitized at high temperature to obtain a macroscopic block composite material with light weight, high strength and toughness, and multifunctional integration. The carbon nanotube-graphene multidimensional hybrid reinforcement replaces the traditional carbon fiber reinforcement to prepare a new type of light and high-performance carbon-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is an optical photograph of the carbon nanotube / graphene / pyrolytic carbon prepared in Example 1 of the present invention;
[0041] Figure 2 This is a 50 μm SEM photograph of the carbon nanotube / graphene / pyrolytic carbon prepared in Example 1 of the present invention;
[0042] Figure 3 This is a 5 μm SEM photograph of the carbon nanotube / graphene / pyrolytic carbon prepared in Example 1 of the present invention;
[0043] Figure 4 This is a diagram showing the mechanical properties of carbon nanotubes / graphene / pyrolytic carbon prepared according to an embodiment of the present invention. DETAILED DESCRIPTION
[0044] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0045] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0046] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0047] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0048] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0049] The invention provides a carbon nanotube / graphene / pyrolytic carbon composite material and a preparation method thereof.
[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0051] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0052] The present invention provides a method for preparing a carbon nanotube / graphene / pyrolytic carbon composite material, comprising the following steps:
[0053] Step 1) Preparation of graphene / nickel foam:
[0054] The nickel foam is first placed in dilute hydrochloric acid (1-2M) for a first treatment, and then placed in acetone (concentration of 13.5 mol / L) for a second treatment to obtain a pretreated nickel foam;
[0055] The pretreated nickel foam is placed in a tube furnace for heat treatment, and a carbon source is introduced to obtain graphene / nickel foam.
[0056] Step 2) In situ growth of carbon nanotubes in graphene / nickel foam using an injection chemical vapor deposition process to obtain carbon nanotube / graphene / nickel foam:
[0057] Dissolving ferrocene in a mixed solution of anhydrous ethanol, ethylenediamine and deionized water and stirring the mixture sufficiently to obtain a growth precursor solution for growing carbon nanotubes;
[0058] The graphene / nickel foam is placed in a tube furnace for heat treatment, and a precursor liquid for growing carbon nanotubes is injected into the graphene / nickel foam by an injection chemical vapor deposition process to obtain a carbon nanotube / graphene / nickel foam;
[0059] With the help of chemical vapor deposition, the in-situ growth of graphene foam and carbon nanotubes with specific morphology and structure was successfully achieved; the controllable preparation of graphene and carbon nanotubes in large-sized porous nickel foam was achieved.
[0060] Step 3) placing the carbon nanotube / graphene / nickel foam in an acid solution, then continuously washing away the residual acid solution, and freeze-drying to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement, thereby constructing a macroscopic carbon nanotube-graphene multidimensional hybrid reinforcement.
[0061] Step 4) Using the carbon nanotube / graphene multidimensional hybrid reinforcement as a matrix, pyrolytic carbon is filled by using a precursor impregnation and pyrolysis method to prepare a carbon nanotube / graphene / pyrolytic carbon composite material.
[0062] The phenolic resin is dissolved in ethanol to obtain a precursor solution of a deposited pyrolytic carbon matrix; the carbon nanotube / graphene multidimensional hybrid reinforcement is immersed in the precursor solution and solidified, and then placed in a tubular furnace for high-temperature cracking to obtain a carbon nanotube / graphene / pyrolytic carbon composite material.
[0063] By controlling the morphology and adjusting the structure of the carbon nanotube-graphene multidimensional hybrid reinforcement, the microstructure of the carbon nanotube / graphene / pyrolytic carbon composite material can be regulated, and the comprehensive performance of the carbon nanotube / graphene / pyrolytic carbon composite material can be improved through effective regulation of the structure.
[0064] Specifically:
[0065] In step 1), the nickel foam is placed in dilute hydrochloric acid and acetone for 5 to 10 minutes respectively, and deionized water is ultrasonicated for 5 to 10 minutes. The heat treatment temperature is 950 to 1100°C, the heat treatment time is 3 to 10 minutes, the carbon source in the heat treatment is any one of methane or methanol, and the concentration of the carbon source in the heat treatment is 0.5 to 3% of the total concentration of the mixed atmosphere; the mixed atmosphere in the heat treatment is a mixed gas of carbon source and hydrogen; the carbon source gas flow rate is 5 to 30 sccm.
[0066] In step 2), the volume ratio of anhydrous ethanol to ethylenediamine is 4:1 to 7:5. The molar ratio of ferrocene to deionized water is 1:10 to 10:1; the concentration of ferrocene is 0.02 to 0.032 g / ml; the injection rate is 5 to 10 ml / h, the heat treatment temperature is 950 to 1100°C, and the heat treatment time is 0.5 to 12 hours; the concentration of the carbon source in the heat treatment is 0.5 to 3% of the total concentration of the mixed atmosphere; the heat treatment temperature is 950 to 1100°C; the heat treatment reaction time is 0.5 to 12 hours;
[0067] In step 3), the carbon nanotube / graphene / nickel foam is placed in a hydrochloric acid water bath at 40-60° C. for etching for 24-48 hours. A vacuum freeze drying process is selected, and the vacuum freeze drying treatment time is 12-48 hours.
[0068] In step 4), the precursor impregnation and cracking process:
[0069] A phenolic resin / ethanol mixed solution is used as a precursor solution of a pyrolytic carbon matrix, and the prepared carbon nanotube / graphene multidimensional hybrid reinforcement is immersed in the precursor solution, wherein the mass fraction of the phenolic resin in the phenolic resin / ethanol mixed solution is 20-50%, and the immersion time is 1-4 hours.
[0070] The impregnated carbon nanotube / graphene multidimensional hybrid reinforcement is then placed in an oven for curing, wherein the oven temperature is 60-200° C. and the curing time is 3-5 hours.
[0071] Finally, the solidified carbon nanotube / graphene multidimensional hybrid reinforcement is placed in a tubular furnace with argon, nitrogen or a mixed atmosphere for high-temperature pyrolysis to obtain a carbon nanotube / graphene / pyrolytic carbon composite material, wherein the high-temperature pyrolysis temperature is 800-1100° C. and the high-temperature pyrolysis time is 0.5-3 h.
[0072] Preferably, the present invention provides a method for preparing a carbon nanotube / graphene / pyrolyzed carbon composite material, comprising the following steps:
[0073] Step 1, growing graphene on nickel foam by chemical vapor deposition to obtain graphene / nickel foam; treating the nickel foam in dilute hydrochloric acid and acetone in turn to obtain pretreated nickel foam;
[0074] The pretreated nickel foam is placed in a tube furnace for heat treatment, and a carbon source is introduced to obtain graphene / nickel foam;
[0075] Among them, the carbon source is introduced to generate graphene, and the specific process is: methane or methanol is used as the carbon source, and the concentration of the carbon source accounts for 0.5-3% of the total concentration of the mixed atmosphere; the graphene generation temperature is 950-1100°C; the chemical vapor deposition time is 3-10 minutes; the mixed atmosphere is a mixed atmosphere of methane and hydrogen.
[0076] Step 2, in situ growing carbon nanotubes in the graphene / nickel foam by injection chemical vapor deposition process to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement;
[0077] Ferrocene is dissolved in a mixed solution of anhydrous ethanol, ethylenediamine and deionized water and stirred sufficiently to obtain an injection solution for growing carbon nanotubes, wherein the volume ratio of anhydrous ethanol to ethylenediamine is 4:1 to 7:5. The molar ratio of ferrocene to deionized water is 1:10 to 10:1; the graphene / nickel foam is placed in a tube furnace for heat treatment, and the injection solution for growing carbon nanotubes is injected into the graphene / nickel foam to obtain carbon nanotube / graphene / nickel foam; the carbon nanotube / graphene / nickel foam is placed in an acid solution, and then the residual acid solution is continuously washed away, and the carbon nanotube / graphene multidimensional hybrid reinforcement is obtained after freeze drying.
[0078] Among them, the graphene / nickel foam is placed in a tube furnace for heat treatment, and the specific process is:
[0079] Any one of toluene, ethanol and acetone is used as a carbon source, and the concentration of the carbon source accounts for 0.5-3% of the total concentration of the mixed atmosphere; the heat treatment temperature is 950-1100° C.; the reaction time is 0.5-12 hours;
[0080] The mixed atmosphere is a mixed gas of any one of toluene, ethanol, acetone and hydrogen.
[0081] Step 3, using a precursor impregnation and pyrolysis method to fill pyrolytic carbon into the reinforcement to obtain a carbon nanotube / graphene / pyrolytic carbon composite material.
[0082] The specific method is:
[0083] The phenolic resin is dissolved in ethanol and mixed and dissolved thoroughly to obtain a precursor solution for depositing a pyrolytic carbon matrix, wherein the mass concentration of the phenolic resin / ethanol is 20% to 50%;
[0084] The carbon nanotube / graphene multidimensional hybrid reinforcement is immersed in a precursor solution composed of a phenolic resin / ethanol solution, placed in an oven for curing, and finally placed in a tubular furnace for high-temperature cracking to obtain a carbon nanotube / graphene / pyrolytic carbon composite material.
[0085] Preferably, the process conditions for curing in an oven are: oven temperature of 60-200°C, holding time of 3-5h. Preferably, the process conditions for high temperature cracking are: high temperature cracking temperature of 800-1100°C, time of 0.5-3h, atmosphere of argon, nitrogen or a mixture of the two.
[0086] The invention also discloses a carbon nanotube / graphene / pyrolytic carbon composite material, which is prepared by using the preparation method.
[0087] Preferably, the composite material has an apparent density of 1.4 to 1.8 g / cm3 and a porosity of 3 to 17%.
[0088] The ultimate compressive strength of the carbon nanotube / graphene / pyrolytic carbon composite material is 130.7 MPa.
[0089] The density of the carbon nanotube / graphene / pyrolytic carbon composite material is 1.4-1.8 g / cm3.
[0090] The porosity of the carbon nanotube / graphene / pyrolytic carbon composite material is 3-17%.
[0091] Embodiment 1:
[0092] First, the cut nickel foam is placed in dilute hydrochloric acid (1M), and then placed in an ultrasonic cleaner for ultrasonic treatment. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0093] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 1080°C, and methane was introduced with a gas flow rate of 5 sccm. The carbon source concentration was 0.5% of the total concentration of the mixed gas. After growing for 3 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0094] Weigh 0.5 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine is 4:1, and then add 0.5 ml of deionized water, the molar ratio of ferrocene to deionized water is 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration is 0.02 g / ml.
[0095] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, toluene was introduced with a gas flow rate of 5 sccm, and the carbon source concentration was 0.5% of the total concentration of the mixed gas. The temperature was raised to a growth temperature of 1080°C, and a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h. After growing for 30 minutes, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0096] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (10M), then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 24 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0097] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is impregnated in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 20% by mass, and the impregnation time is 1 hour. The preform is then placed in an oven for curing, wherein the oven temperature is 100°C, the curing time is 1 hour, and then it is adjusted to 180°C for curing for 3 hours and then taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 900°C, and the high-temperature cracking time is 0.5 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0098] Embodiment 2:
[0099] First, the cut nickel foam is placed in dilute hydrochloric acid (1.3M), and then placed in an ultrasonic cleaner for ultrasonication. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0100] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 1080°C, and methane was introduced with a gas flow rate of 11 sccm. The carbon source concentration was 1.1% of the total concentration of the mixed gas. After growing for 3 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0101] Weigh 0.6 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine is 4:1, and then add 0.6 ml of deionized water, the molar ratio of ferrocene to deionized water is 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration is 0.024 g / ml.
[0102] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, toluene was introduced with a gas flow rate of 11 sccm, and the carbon source concentration was 1.1% of the total concentration of the mixed gas. The temperature was raised to a growth temperature of 1080°C, and a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h. After growing for 30 minutes, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0103] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (11M), then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 24 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0104] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is impregnated in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 20% by mass, and the impregnation time is 1 hour. The preform is then placed in an oven for curing, wherein the oven temperature is 100°C, the curing time is 1 hour, and then it is adjusted to 180°C for curing for 3 hours and then taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 900°C, and the high-temperature cracking time is 0.5 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0105] The test results show that the density is 1.58g / cm3, the porosity is 3.63%, and the compressive strength is 93.7MPa.
[0106] Embodiment 3:
[0107] First, the cut nickel foam is placed in dilute hydrochloric acid (1.5M), and then placed in an ultrasonic cleaner for ultrasonic treatment. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0108] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 1080°C, and methane was introduced with a gas flow rate of 20 sccm. The carbon source concentration was 2% of the total concentration of the mixed gas. After growing for 3 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0109] Weigh 0.7 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine is 4:1, and then add 0.7 ml of deionized water, the molar ratio of ferrocene to deionized water is 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration is 0.028 g / ml.
[0110] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, toluene was introduced with a gas flow rate of 20 sccm, the carbon source concentration was 2% of the total concentration of the mixed gas, the temperature was raised to a growth temperature of 1080°C, a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h, and after growing for 30 minutes, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0111] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (12M), and then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 24 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0112] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is impregnated in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 20% by mass, and the impregnation time is 1 hour. The preform is then placed in an oven for curing, wherein the oven temperature is 100°C, the curing time is 1 hour, and then it is adjusted to 180°C for curing for 3 hours and then taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 900°C, and the high-temperature cracking time is 0.5 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0113] The test results show that the density is 1.60g / cm3, the porosity is 3.44%, and the compression strength can reach 133.7MPa.
[0114] Embodiment 4:
[0115] First, the cut nickel foam is placed in dilute hydrochloric acid (2M), and then placed in an ultrasonic cleaner for ultrasonic treatment. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0116] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 1080°C, and methane was introduced with a gas flow rate of 5 sccm. The carbon source concentration was 3% of the total concentration of the mixed gas. After growing for 3 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0117] Weigh 0.8 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine being 4:1, then add 0.8 ml of deionized water, the molar ratio of ferrocene to deionized water being 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration being 0.032 g / ml.
[0118] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, toluene was introduced with a gas flow rate of 30 sccm, the carbon source concentration was 3% of the total concentration of the mixed gas, the temperature was raised to a growth temperature of 1080°C, a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h, and after growing for 30 minutes, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0119] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (13M), and then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 24 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0120] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is impregnated in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 20% by mass, and the impregnation time is 1 hour. The preform is then placed in an oven for curing, wherein the oven temperature is 100°C, the curing time is 1 hour, and then it is adjusted to 180°C for curing for 3 hours and then taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 900°C, and the high-temperature cracking time is 0.5 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0121] The test results show that the density is 1.55g / cm3 and the porosity is 3.74%. However, compared with Example 1 and Example 3, as the carbon nanotube content increases, the compressive strength shows a downward trend and becomes 113.6MPa. This is because more carbon nanotubes are prone to agglomeration, which is not conducive to the densification of the composite material, resulting in an increase in closed pores in the composite material, cracks are easily generated and propagated, and the reinforcement effect is reduced.
[0122] Embodiment 5:
[0123] First, the cut nickel foam is placed in dilute hydrochloric acid (1M), and then placed in an ultrasonic cleaner for ultrasonic treatment. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0124] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 950°C, and methanol was introduced with a gas flow rate of 5 sccm. The carbon source concentration was 0.5% of the total concentration of the mixed gas. After growing for 10 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0125] Weigh 0.5 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine being 7:5, then add 0.5 ml of deionized water, the molar ratio of ferrocene to deionized water being 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration being 0.02 g / ml.
[0126] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, ethanol was introduced with a gas flow rate of 5 sccm, and the carbon source concentration was 0.5% of the total concentration of the mixed gas. The temperature was raised to a growth temperature of 950°C, and a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h. After growing for 12 hours, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0127] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (10M), then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 12 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0128] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is immersed in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 50% by mass, and the immersion time is 1 hour. The preform is then placed in an oven for curing, wherein the oven temperature is 60°C, the curing time is 1 hour, and then it is adjusted to 200°C for curing for 2 hours and then taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 800°C, and the high-temperature cracking time is 3 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0129] Embodiment 6:
[0130] First, the cut nickel foam is placed in dilute hydrochloric acid (1M), and then placed in an ultrasonic cleaner for ultrasonic treatment. After 5 minutes, the nickel foam is taken out and then placed in acetone for treatment for 10 minutes. After taking it out, it is washed with deionized water and ultrasonicated for 5 minutes. After taking it out, it is dried at room temperature to obtain the pretreated nickel foam.
[0131] The pretreated nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, and hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm. The temperature was raised to a growth temperature of 1100°C, and methanol was introduced with a gas flow rate of 5 sccm. The carbon source concentration was 0.5% of the total concentration of the mixed gas. After growing for 8 minutes, it was quickly pulled out of the heating zone to instantly cool down to generate graphene, thereby obtaining graphene / nickel foam.
[0132] Weigh 0.5 g of ferrocene and add it to 25 ml of a mixed solution of anhydrous ethanol and ethylenediamine, the volume ratio of anhydrous ethanol to ethylenediamine being 4:5, then add 0.5 ml of deionized water, the molar ratio of ferrocene to deionized water being 1:10, to obtain an injection solution for growing carbon nanotubes, the ferrocene concentration being 0.02 g / ml.
[0133] The graphene / nickel foam was placed in a tubular furnace for heat treatment. Argon was used as a carrier gas with a fixed flow rate of 900 sccm, hydrogen was used as a reducing gas with a fixed flow rate of 100 sccm, acetone was introduced with a gas flow rate of 5 sccm, and the carbon source concentration was 0.5% of the total concentration of the mixed gas. The temperature was raised to a growth temperature of 1100°C, and a growth precursor liquid was injected into the tube mouth using a CNC syringe with an injection rate of 10 ml / h. After growing for 12 minutes, the temperature was lowered with the furnace to obtain carbon nanotubes / graphene / nickel foam.
[0134] The prepared carbon nanotube / graphene / nickel foam was placed in concentrated hydrochloric acid (10M), then heated in a water bath, and the foamed nickel was etched in a water bath at 60°C for 48 hours. The operation was repeated 4 times, and the foam was placed in a vacuum freeze dryer for 48 hours to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement.
[0135] The phenolic resin / ethanol mixed solution is used as the precursor solution of the pyrolytic carbon matrix, and the prepared reinforcement is impregnated in the mixed solution, wherein the concentration of the phenolic resin in the phenolic resin / ethanol mixed solution is 30% by mass, and the impregnation time is 1 hour. Then the preform is placed in an oven for curing, wherein the oven temperature is 200°C, the curing time is 2 hours, and it is further adjusted to 200°C for curing for 3 hours before being taken out, and then placed in a tubular furnace with nitrogen for high-temperature heat treatment, wherein the high-temperature cracking temperature is 1100°C, and the high-temperature cracking time is 3 hours. The above-mentioned impregnation, curing and high-temperature heat treatment steps are repeated, and the precursor is impregnated, cracked and filled with pyrolytic carbon until it is densified, and a carbon nanotube / graphene / pyrolytic carbon composite material can be obtained.
[0136] Depend on Figure 1 It can be seen that carbon nanotube / graphene / pyrolytic carbon composite materials can be prepared in large quantities. Figure 2 , Figure 3 It can be seen that the prepared carbon nanotube / graphene / pyrolytic carbon composite microstructure has a strengthened graphene-pyrolytic carbon interface due to the growth of carbon nanotubes, and has a strong carbon nanotube-pyrolytic carbon interface, which will greatly improve the mechanical properties of the material. Figure 4 It can be seen that the carbon nanotube / graphene / pyrolytic carbon composite material has excellent mechanical properties.
[0137] The present invention provides a carbon nanotube / graphene / pyrolytic carbon composite material and a preparation method thereof, which has the advantages of light weight, high strength and toughness, and multifunctional integration. Specifically, a macroscopic three-dimensional skeleton of graphene / nickel foam is used, and then carbon nanotubes are in situ grown in the graphene / nickel foam by injection chemical vapor deposition to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement with graphene foam as a reinforcement skeleton and carbon nanotubes interspersed in the foam micropores. The carbon nanotube / graphene multidimensional hybrid reinforcement is densified by chemical vapor infiltration, and finally graphitized at high temperature to obtain a macroscopic block composite material with light weight, high strength and toughness, and multifunctional integration.
[0138] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a carbon nanotube / graphene / pyrolytic carbon composite material, characterized in that: The following steps are involved: S1: preparing graphene / nickel foam; S2: In situ growth of carbon nanotubes in graphene / nickel foam by injection chemical vapor deposition to obtain carbon nanotube / graphene multidimensional hybrid reinforcement; S3: Filling pyrolytic carbon into the carbon nanotube / graphene multidimensional hybrid reinforcement by precursor impregnation pyrolysis method to prepare carbon nanotube / graphene / pyrolytic carbon composite material; In S2, the process of in-situ growing carbon nanotubes in graphene / nickel foam by injection chemical vapor deposition to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement is as follows: S21: mixing anhydrous ethanol, ethylenediamine and deionized water uniformly to obtain a mixed solution, and then dissolving ferrocene in the mixed solution to obtain a precursor solution for growing carbon nanotubes; S22: placing the graphene / nickel foam in a tube furnace for a second heat treatment, injecting a precursor liquid for growing carbon nanotubes into the graphene / nickel foam to obtain a carbon nanotube / graphene / nickel foam; S23: washing the carbon nanotube / graphene / nickel foam and freeze-drying it to obtain a carbon nanotube / graphene multidimensional hybrid reinforcement; In S21, the volume ratio of anhydrous ethanol to ethylenediamine is (4-7):(1-5), the concentration of ferrocene is 0.02-0.032 g / ml; and the molar ratio of ferrocene to deionized water in the mixed solution is (1-10):(1-10).
2. The method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to claim 1, characterized in that: In S1, the method for preparing graphene / nickel foam is chemical vapor deposition, and the process of preparing graphene / nickel foam by chemical vapor deposition is as follows: S11: placing the nickel foam in hydrochloric acid for a first treatment, and then placing it in acetone for a second treatment to obtain a pretreated nickel foam; S12: placing the pretreated nickel foam in a tubular furnace for a first heat treatment, growing graphene on the pretreated nickel foam, and obtaining graphene / nickel foam.
3. The method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to claim 2, characterized in that: In S12, the process of the first heat treatment is as follows: The carbon source in the first heat treatment is methane or methanol, and the concentration of the carbon source in the first heat treatment is 0.5-3% of the total concentration of the mixed atmosphere; the mixed atmosphere in the first heat treatment is a mixed gas composed of the carbon source and hydrogen; The growth temperature during the graphene growth process is 950-1100° C.; The first heat treatment time is 3~10min.
4. The method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to claim 1, characterized in that: In S22, the process of the second heat treatment is as follows: The carbon source in the second heat treatment is any one of toluene, ethanol, and acetone; the mixed atmosphere in the second heat treatment is a mixed gas composed of a carbon source and hydrogen; the concentration of the carbon source in the second heat treatment is 0.5-3% of the total concentration of the mixed atmosphere; the heat treatment temperature in the second heat treatment is 950-1100° C.; the reaction time in the second heat treatment is 0.5-12 h; In S23, the freeze-drying process time is 12 to 48 hours.
5. The method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to claim 1, characterized in that: In S3, the process of filling pyrolytic carbon in the carbon nanotube / graphene multidimensional hybrid reinforcement by the precursor impregnation pyrolysis method to prepare the carbon nanotube / graphene / pyrolytic carbon composite material is as follows: S31: dissolving phenolic resin in ethanol to obtain a precursor solution for depositing a pyrolytic carbon matrix; S32: Immersing the carbon nanotube / graphene multidimensional hybrid reinforcement in a precursor solution for curing, and then placing it in a tubular furnace for high-temperature cracking to obtain a carbon nanotube / graphene / pyrolytic carbon composite material.
6. The method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to claim 5, characterized in that: In S31, the concentration of the phenolic resin in the precursor solution is 20-50% by mass; In the S32, the process conditions of the curing are as follows: The curing is performed by oven curing; the oven curing temperature is 60-200°C; the oven curing holding time is 3-5 hours; In S32, the process conditions of the high temperature cracking are as follows: The temperature of the high temperature cracking is 800-1100°C, the time of the high temperature cracking is 0.5-3 h, and the atmosphere of the high temperature cracking is argon, nitrogen, or a mixture of the two in any ratio.
7. A carbon nanotube / graphene / pyrolytic carbon composite material prepared by the method for preparing the carbon nanotube / graphene / pyrolytic carbon composite material according to any one of claims 1 to 6.
8. The carbon nanotube / graphene / pyrolytic carbon composite material according to claim 7, characterized in that: The apparent density of the carbon nanotube / graphene / pyrolyzed carbon composite material is 1.4-1.8 g / cm 3 ; The porosity of the carbon nanotube / graphene / pyrolytic carbon composite material is 3~17%.
Citation Information
Patent Citations
Method for preparing three-dimensional graphene-carbon nitrogen nanotube composite
CN102745679A
Reinforced reduced graphene oxide / carbon nanotube / pyrolytic carbon composite material and preparation method thereof
CN115744887A